The first record of Pyrgus malvoides (Elwes & Edwards, 1897) in the Czech Republic (Lepidoptera, Hesperiidae): an accidental introduction? - Vladimír Hula; Jana Niedobová (Nota Lepidopterologica, 2014)
The Mediterranean skipper, Pyrgus malvoides (Elwes & Edwards, 1897), is newly recorded for the Czech Republic, some 400 km away from its nearest known population. The specimen was collected in June 1993 in Hejná, Bohemia and was discovered in the collection of Oldřich Jakeš during a revision of other Pyrgus species. The presence of this species elsewhere in the region could not be established and the best current explanation for this record is that it was an accidental introduction.